CONSIDERING THE PECULIARITIES OF DEFORMATION MODELS IN CALCULATING THE STRENGTH OF FLEXURAL CONCRETE ELEMENTS IN NORMAL CROSS SECTIONS SNIP 2.03.01-84 - , А. М. (Municipal economy of cities. Series: «Economy science», 2013)
The technique taking into account the deformation characteristics of model calculations in the normal strength of the section in bending by SNIP 2.03.01-84.